The Influence of the Discovery Learning Learning Model on Student Learning Outcomes in Class V Citizenship Education Learning at State Elementary School 39 Pekanbaru - Putri Atika Suri; Munjiatun Munjiatun; Intan Kartika Sari (CV. Rayyan Dwi Bharata, 2024)
This research aims to describe the influence of the Discovery Learning learning model on class V. This research was carried out in classes VB and VC at SDN 39 Pekanbaru with a total of 46 people. This research was carried out in the odd semester of the 2022/2023 academic year, to be precise in September 2023. This research used an experimental research type with the Non Equivalent Control Group Design method. The assessment in this study used objective tests in the form of PKN questions. After these questions were created, the researcher tested the questions on a class that had studied the material on the practice of Pancasila values in daily life with 30 students in class VI of SD Negeri 39 Pekanbaru. Next, the researcher tested the validity, reliability, level of difficulty and distinguishing power of the questions. After the pretest and posttest questions were declared usable, the researcher then gave the pretest questions to the experimental class and control class. When the research data has been obtained, the researcher carries out data analysis such as descriptive analysis, normality test, homogeneity test, and hypothesis test, N-Score test. The average pretest score in the experimental class was 36.087 while in the control class it was 83.5652. After carrying out the pretest for both classes, the researcher carried out learning according to the Learning Implementation Plan (RPP). Then the final stage is to give a posttest to the two classes. The average posttest score for students in the experimental class was 83.5652, while in the control class it was 71.7391. Based on data testing, the pretest and posttest results were normally and homogeneously distributed. Because the data is normally distributed, the researcher tested the hypothesis using the t-test, and obtained significant data results where 0.000 0.05 means Ha is accepted or in the sense that the Discovery Learning learning model has a significant effect on student learning outcomes. So the conclusion of this research is that the Discovery Learning model has an influence on student learning outcomes in class V citizenship education at Pekanbaru 39 State Elementary School.